2012
DOI: 10.4103/0972-2327.100023
|View full text |Cite
|
Sign up to set email alerts
|

Tension type headache

Abstract: Tension type headaches are common in clinical practice. Earlier known by various names, the diagnosis has had psychological connotations. Recent evidence has helped clarify the neurobiological basis and the disorder is increasingly considered more in the preview of neurologists. The classification, clinical features, differential diagnosis and treatment of tension type headache are discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…Fotofobia e a fonofobia podem estar presentes ou não 2 . É o mais prevalente tipo de cefaleia dentre todas as faixas etárias ao redor do mundo 6,7 .…”
Section: Introductionunclassified
“…Fotofobia e a fonofobia podem estar presentes ou não 2 . É o mais prevalente tipo de cefaleia dentre todas as faixas etárias ao redor do mundo 6,7 .…”
Section: Introductionunclassified
“…1,2 The prevalence of TTH, which seems to be higher in Europe (80%) than in Asia or America (20%-30%), is estimated at approximately 40% globally. 4 TTH is the most frequent type of primary headache; the International Headache Society further classifies it into infrequent episodic, frequent episodic, and chronic TTH. 4 TTH is the most frequent type of primary headache; the International Headache Society further classifies it into infrequent episodic, frequent episodic, and chronic TTH.…”
Section: Introductionmentioning
confidence: 99%
“…5 A community-based study conducted in Singapore found that episodic tension-type headache (ETTH) and chronic tension-type headache (CTTH) accounted for 39.9 percent and 2.4 percent of headaches, respectively. 2 Absenteeism resulting from TTH is considerable, 6 with a loss of 4.2 workday equivalents per year. 7,8 TTH also results in repeated emergency department and clinic visits.9,10 Pharmacological treatment includes oral analgesics such as aspirin, acetaminophen, and non-steroidal anti-in ammatory drugs (NSAIDS) in acute attacks.…”
Section: Introductionmentioning
confidence: 99%